Peculiarities of Investment Portfolio Management in the Context of Globalisation Changes (Economics and region, 2023)
The article analyses changes in approaches to investment in the period of globalisation and digitalisation of world economies. It is found that investments can take various forms, including the purchase of shares or bonds, investment in real estate or starting a new business. Certainly, investing is an unpredictable and risky process, as it does not always result in a return on the invested amount. It has been proven that successful investing requires a combination of knowledge, research and risk management. It is important to understand the potential risks and rewards associated with any investment before investing your own money, and to diversify your investments to minimise exposure to any particular asset or market. The authors found that cryptocurrencies and stocks are two popular investment options that have both advantages and disadvantages. The study found that cryptocurrency, as a digital or virtual currency, uses encryption techniques to regulate the generation of currency units and verify the transfer of funds, and the most popular cryptocurrency is Bitcoin. Cryptocurrencies operate independently of central banks and are decentralised, so the value of cryptocurrencies is determined by market supply and demand. The article shows that digital currencies are not a reliable means of saving and a measure of value due to high exchange rate volatility. The main factors affecting the value of cryptocurrencies are the ratio of supply and demand, investor sentiment and market factors. The features of investing in joint stock companies are studied. Accordingly, by purchasing shares in a company, a person can become a partial owner of the company and have rights to its assets and profits. The value of each share is determined by the constituent documents, as the nominal value of one share must be the same. A comparison of investments in cryptocurrencies and stocks has shown that an optimal investment portfolio should consist of a wide range of assets and be designed for the long term. The optimal portfolio should consist of shares of the largest and most stable companies, as well as cryptocurrencies: Bitcoin and Ethereum. It is proved that in order to increase profits and minimise possible losses in wartime, it is important to have a long-term investment strategy and a diversified portfolio that can withstand temporary market fluctuations.
Keywords: investments; investing; cryptocurrency; stocks; investment portfolio management; digitalisation